SIMPANAN KARBON DUA JENIS VEGETASI HUTAN KERING TROPIKA DI WILAYAH SEMI ARID NUSA TENGGARA TIMUR - Aah Ahmad Almulqu (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
Dry forests in semi-arid region plays important roles in humans’ life, whether it is socially, economically, or ecologically. Most of the time, it is very difficult to maintain the equilibrium of those roles, especially in developing-country where the economic role is more exploited than the other roles. This mismanagement of forests would lead to the situation where the forest will be in rapid retreat. On the other hand, maintaining as well as increasing the forests is the most essential solution for climate change, as forests play integral part on carbon sequestration therefore stabilizing the climate. In carbon sequestration, plants incorporate carbon from atmospheric carbon dioxide (CO2) through photosynthesis then storing it in biomass and soil. As each vegetation has different capacity to store carbon, this study tries to estimate the absorption rate of carbon dioxide (CO2) and the potential carbon storage of Borneo camphor (Dryobalanops aromatica) and Kesambi (Schleichera oleosa) in Oebatu Dano Ina forest (RTK.24) Pantai Baru sub-district, Rote Ndao district, Nusa Tenggara Timur province. The result shows carbon storage range of 6.51–42.998 ton/ha for both vegetation with average of 0,135–1,791 ton/ha for each tree, while the average of carbon dioxide (CO2) absorption rate is 0,498–6,575 ton/ha for each tree.